PERHITUNGAN ESTIMASI WAKTU PADA PRODUKSI BARANG DENGAN MENERAPKAN ALGORITMA NAIVE BAYES KLASIFKASI (STUDI KASUS PT. HASIL RAYA INDUSTRIES) - Wijayanti, Rima Rizqi; Abdurrasyid, Abdurrasyid (Jurnal Informatika, 2021)
PT. Hasil Raya Industries is a company engaged in the manufacture of plastic gods such as bottles of packaging. During this time there is difficulty in calculating the estimated duration of the product work. Because the calculation of estimation is still manual, not well recorded and not accurate. To support the estimation of production time, a web-based system is designed to solve the problem. The authors apply the Naive Bayes algorithm based on Data Demand Goods and Production Data Data at PT. Hasil Raya Industries to give solution in finding time estimation at work of goods production This application can run well and can produce information as expected. By using the application time of production of goods, PT.Hasil Raya Industries can directly receive reports of estimation results of production time.Â Â Â